Alleviating arsenic stress affecting the growth of Vigna radiata through the application of Klebsiella strain ASBT-KP1 isolated from wastewater - Prasad, Megha; Madhavan, Ajith; Babu, Pradeesh; Salim, Amrita; Subhash, Suja; Nair, Bipin G.; Pal, Sanjay (Frontiers in Microbiology, 2024)
Arsenic contamination of soil and water is a major environmental issue. Bioremediation through plant growth-promoting bacteria is viable, cost-effective, and sustainable. Along with arsenic removal, it also improves plant productivity under stressful conditions. A crucial aspect of such a strategy is the selection of bacterial inoculum. The described study demonstrates that the indigenous wastewater isolate, ASBT-KP1, could be a promising candidate. Identified as Klebsiella pneumoniae, ASBT-KP1 harbours genes associated with heavy metal and oxidative stress resistance, production of antimicrobial compounds and growth-promotion activity. The isolate efficiently accumulated 30 µg/g bacterial dry mass of arsenic. Tolerance towards arsenate and arsenite was 120 mM and 70 mM, respectively. PlantP lant biomass content of Vigna radiata improved by 13 % when grown in arsenic-free soil under laboratory conditions in the presence of the isolate. The increase became even more significant under the same conditions in the presence of arsenic, recording a 37 % increase. The phylogenetic analysis assigned ASBT-KP1 to the clade of Klebsiella strains that promote plant growth. Similar results were also observed in Oryza sativa, employed to assess the ability of the strain to promote growth, in plants other than V. radiata. This study identifies a prospective candidate in ASBT-KP1 that could be employed as a plant growth-promoting rhizoinoculant in agricultural practices.